On Threats to Economic Security in a Risk Society - Leszczyński, Marek (Journal of Finance and Financial Law, 2024)
The purpose of the article. The aim of the article is to analyze and diagnose economic security in the context of holistically understood social challenges. The main research problem addressed in the article is the intensification of economic threats in the conditions of the transition to financial capitalism and the increasing social costs of the risk of this transition. Methodology. The article mainly uses literature studies, descriptive and narrative methods. Results of the research. Excessive liberalization of financial markets has brought more losses than benefits, the value of work and the idea of full employment have been forgotten. Most people in the world earn their living from income from work, meanwhile the imbalance between the manufacturing and financial sectors has resulted in a decline in income from work and forced the vast majority of workers who want to maintain or increase consumption to take out loans and credits. Consumption is growing, but household debt is growing. The financial sector has grown beyond measure, disturbing the basis for rational decision-making by consumers – based on the actual, real value of disposable income.